In silico identification of Single Nucleotide Polymorphisms in the Varroa destructor Cytochrome c Oxidase Subunit 1 (cox1) and Cytochrome b (cytb) genes, haplotype analysis, and assessment of population structure - Kilinc, Seyma Gunyakti; Celik, Figen; Kesik, Harun Kaya; Simsek, Sami (Wiley, 2025)
Varroa destructor is an ectoparasite that has been identified as the primary pathogen of the western honey bee, Apis mellifera, globally. Investigating the genetic variations of this mite in different geographical regions is crucial for understanding its population dynamics and evolutionary potential. Genetic diversity data are essential for tracking its spread, identifying emerging lineages, and developing effective control strategies. The objective of this study was to investigate haplotype diversity, genetic variation and population structure by in silico phylogenetic analysis of mitochondrial cox1 and cytb gene sequences of V. destructor isolates submitted to GenBank from different regions of the world. For this purpose, 509 sequences covering 399 bp of the cox1 gene region and 215 sequences covering 628 bp of the cytb gene region were used for the analyses. A total of 37 polymorphic sites and 24 haplotypes were identified in the cox1 sequences, while 31 polymorphic sites and 23 haplotypes were observed in the cytb region. Both gene regions exhibited high negative values for diversity and neutrality indices, indicating possible recent population expansion or selective pressures. This study also evaluated single nucleotide polymorphisms (SNPs) within GenBank-derived sequences and analysed their impact on haplotype differentiation and population structure. The results revealed considerable haplotype diversity, including several region-specific variants and potential signs of recent population expansion. The findings highlight ongoing microevolution within V. destructor populations, likely driven by host movement, acaricide use and ecological pressures. These insights are vital for apiculture, as the spread of genetically diverse and potentially more virulent mite lineages could undermine mite control efficacy and honey bee health. Future surveillance efforts should integrate genetic monitoring into management practices to support sustainable beekeeping worldwide.
Keywords: cox1; cytb; haplotype; in silico; Varroa destructor